The Relationship between the Flow Around the Qinghai-Xizang Plateau and the Precipitation and Temperature in China in Winter Half-year - Yongli ZHANG; Hongchao ZUO; Xiaoqing GAO; Shihua LÜ; Bolong CHEN; Longxiang DONG; Licheng LI (Gaoyuan qixiang)
A dynamic southern branch trough （SBT） and a dynamic northern branch ridge （NBR）， two flows around the Tibetan Plateau （FQXP） generated by the mid-latitude westerlies in the winter half-year （October-April）， have an important influence on the weather and climate of their vicinity and downstream.In this paper， differences between the mean vorticity and the multi-year mean vorticity of two key regions-where the SBT and the NBR are located in 600 hPa are used to represent the intensity of the SBT and the NBR separately.Then the difference between the strength of SBT and NBR is defined visually as the intensity index of FQXP.The relationship between the precipitation and temperature in China and the evolution of FQXP's average in winter half-year and that in autumn， winter and spring is discussed， using correlation analysis and composite analysis.The results show that the FQXP is constant in the winter half-year （October-April）， with significant interannual variations， and the strongest in winter.In the context of global warming， variations in the intensity of FQXP at each period is closely related to the precipitation and temperature in Northwest， Southwest and South China， especially in winter.FQXP has a significant relationship with the temperature changes in northwest， southwest and northeast China， and its best precipitation correlations are found in southwest and south China.Analysis of anomalous large-scale atmospheric circulation and physical quantity fields， such as water vapor flux dispersion and vertical velocity， at each layer in each time period leads to the conclusion that the bottom-up positive pressure characteristic is significant in most of Asia， which well explains the relationship between FQXP anomalies and precipitation and temperature in China at each time period.FQXP anomalies may also be one cause for high-impact weather in China during winter half-year.